PERAMPASAN ASET SEBAGAI SANKSI TAMBAHAN : ANALISIS PENGEMBALIAN KERUGIAN NEGARA DALAM PENANGANAN TINDAK PIDANA KORUPSI DI INDONESIA - Lisa Dwi Fitriyanti; Suwandono, Agus (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2025)
Corruption constitutes an extraordinary crime with systemic impacts on state stability and development, requiring non-conventional legal approaches for its enforcement. One of the developing instruments in corruption handling in Indonesia is asset forfeiture as an additional sanction to recover state losses. This research aims to analyze the legal position of asset forfeiture within Indonesia's criminal law system and its implementation mechanism in recovering state losses due to corruption. The Method employed is a juridical-normative approach with analysis of relevant legislation and case studies from court decisions that have obtained permanent legal force. The study results that asset forfeiture, both through criminal mechanisms and non-conventional approaches such as non-conviction bases asset forfeiture, has a strong legal foundation in corruption eradication efforts. However, its implementation still faces obstacles such as regulatory overlaps, weak inter-institutional coordination, and limited asset tracing capacity. The implications of this research emphasize the importance of reformulating asset forfeiture legal policies and strengthening institutions to become an effective instrument for optional state loss recovery.